PREDICTION OF FUEL TEMPERATURE OF AP1000 DUE TO THE FORMATION OF CRUD AND OXIDE LAYER - Isnaini, Muhammad Darwis; Subekti, Muhammad; Sunarya, Geni Rina (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2017)
An analysis to predict the fuel temperature due to crud and oxide layer formed on the hot sub-channel cladding surface of AP1000 reactor has been performed. During reactor operation, the heat transfer and cooling process occur on the fuel cladding surface. During the heat exposure process, an oxide layer and crud are formed on the cladding surface. The decrease of heat transfer performance will increase the fuel and cladding temperatures. Therefore, the effect of fuel temperature increase during the heat exposure process has to be analyzed. The analysis was conducted for nominal power of 3400 MWt using COBRA-EN code, by varying the modular oxide thickness of 0, 20, 40, 60, 80, 100 and 120 mm, crud thickness of 0, 10 and 20 mm and black oxide thickness of 0, 10, 20, 30 and 40 mm. For full cycle hot sub-channel condition, the combination of crud thickness of 20 mm and modular oxide thickness of 115 mm give prediction of the peak fuel center line temperature and the peak cladding surface temperature of 1870.73°C and 609.40°C, respectively. However, the oxide layer is predicted only formed on hot sub-channel during BOC (about 40% of full cycle). The results show that the prediction of the peak fuel center line temperature and the peak cladding surface temperature are 1713.18°C and 451.87°C, respectively. Compared to the normal and fresh fuel conditions, the peak fuel center line temperature and the peak cladding surface temperature increase by 6.53% and 29.86%, respectively.